Deterioration of Phosphate Homeostasis Is a Trigger for Cardiac Afterload ― Clinical Importance of Fibroblast Growth Factor 23 for Accelerated Aging - Yonemitsu, Koichiro; Ishida, Toshifumi; Takai, Seiko; Harada, Eisaku; Kugimiya, Fumihito; Mizuno, Yuji; Nakayama, Yoshiharu (Circulation Reports, 2023)
Background: After the discovery of the Klotho gene, phosphate came into focus as a pathogenetic aging agent. Phosphate homeostasis is controlled by phosphate-regulating hormones: fibroblast growth factor 23 (FGF23), vitamin D3, and parathyroid hormone. This study investigated the relationship between the deterioration in phosphate homeostasis and arterial stiffness by measuring serum FGF23 concentrations.Methods and Results: The study subjects comprised 82 hospitalized patients (31 males, 51 females; mean [±SD] age 78.6±10.5 years). All patients underwent chest computed tomography, measurement of central blood pressure (BP), and blood chemistry tests. Arterial calcification and/or stiffness was evaluated using the Agatston calcification score (ACS) and pulse wave velocity (PWV). PWV was significantly correlated with age (t=23.47, P<0.0001), estimated glomerular filtration rate (eGFR; t=−4.40, P<0.0001), and ACS (t=4.36, P<0.0001). Serum FGF23 concentrations were significantly correlated with age (t=2.52, P=0.014), eGFR (t=−3.37, P<0.001), serum inorganic phosphorus concentrations (t=3.49, P<0.001), serum vitamin D3concentrations (t=−4.57, P<0.001), ACS (t=2.30, P=0.025), augmentation pressure (t=2.48, P=0.015), central systolic BP (t=2.00, P=0.049), plasma B-type natriuretic peptide (BNP) concentrations (t=3.48, P<0.001), and PWV (t=2.99, P=0.004). PWV was positively related to augmentation pressure (t=4.09, P<0.001), central systolic BP (t=3.13, P=0.002), and plasma BNP concentrations (t=3.54, P<0.001).Conclusions: This study shows that the increase in serum FGF23 concentrations reflects deterioration of phosphate homeostasis and is an important predictor for arterial stiffness, which intensifies cardiac afterload.